Effect of blue-blocking glasses in major depressive disorder with sleep onset insomnia: A randomized, double-blind, placebo-controlled study. (3rd July 2017) - Esaki, Yuichi; Kitajima, Tsuyoshi; Takeuchi, Ippei; Tsuboi, Soji; Furukawa, Osamu; Moriwaki, Masatsugu; Fujita, Kiyoshi; Iwata, Nakao
ABSTRACT: Blue wavelengths form the portion of the visible electromagnetic spectrum that most potently regulates circadian rhythm. We hypothesized that wearing blue-blocking (BB) glasses in the evening may influence circadian rhythm disturbances in patients with major depressive disorder (MDD), resulting in improved sleep and mood. We used a randomized placebo-controlled double-blinded design. Patients with MDD with sleep onset insomnia were randomly assigned to wearing either BB glasses or clear glasses (placebo). Patients were instructed to wear the glasses from 20:00 hours until bedtime for 2 weeks. We assessed sleep state (sleep quality on a visual analog scale, the Morningness–Eveningness Questionnaire [MEQ], and a sleep diary) and depressive symptoms at baseline and after 2 weeks. Data were analyzed with a full analysis set. In total, 20 patients were randomly assigned to the BB and placebo groups (BB group, n = 10; placebo group, n = 10). There were three dropouts (BB group, n = 1; placebo group, n = 2). At baseline, sleep quality, sleep latency (assessed via a sleep diary), and antipsychotics use differed between the groups. To take account of these differences, the baseline sleep state or depressive symptoms and antipsychotics use were used as covariates in the later analysis. The change scores for sleep quality did not show a significant improvement in the BB group compared with the placebo group (mean [standard deviation, SD] scores for BB versus placebo: 36.1 [31.7] versus 16.2 [15.1], p = 0.43), although half of the BB group showed a clear improvement in sleep quality. The change in MEQ scores did not significantly differ between the groups ( p = 0.14), although there was a trend of a shift to morning type in the BB group (3.10 [4.95] points) and to evening type in the placebo group (0.50 [3.89] points). There were no statistically significant changes in depressive symptoms in either group. Across both groups, 40% of the participants reported pain or discomfort from wearing the glasses, which were available in only one size. Thus, the failure to find significant differences may have resulted from the glasses used in this study. Glasses fitted to individual patients may improve efficacy and safety. Replication of the study with a larger sample size and size-adjustable glasses is needed.